Traumatic Brain Injury in Young Children: A Scoping Review - Salley, Jessica; Crook, Libby; Ciccia, Angela; Haarbauer-Krupa, Juliet; Lundine, Jennifer P. (Seminars in Speech and Language, 2020)
To review the evidence available on early childhood (i.e., 0–5 years 11 months) traumatic brain injury (TBI) and identify clinical implications and future directions for speech-language pathology (SLP) practice and research, a scoping review of the literature was conducted following the 2018 Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRSIMA-ScR) guidelines. A total of 44 peer-reviewed articles were included for review. Included studies were assigned one or more of the following thematic labels related to early childhood TBI: etiology, assessment, treatment, outcomes, contributing factors. Most of the studies were nonexperimental studies and addressed outcomes following early childhood TBI. We conclude, based on this scoping review, that children who experience a TBI before 6 years of age are at risk for persistent long-term difficulties in academic and social functioning. SLPs are among the group of clinicians most appropriate to assess and treat these children; yet, the evidence for assessment, treatment, and identification of factors contributing to the recovery of young children with TBI is particularly lacking. Rigorous research is needed to improve the evidence base for SLPs.
Keywords: early childhood; traumatic brain injury; speech-language pathology; assessment; treatment